Characteristics of Tidal Channels in a Mesotidal Estuary of Argentina - Ginsberg, Silvia Susana (2004)
Bahía Blanca Estuary is a complex network of tidal channels, extensive tidal flats, low marshes areas and islands. The lack of a large source of sediments either from river or the shelf results in that the tidal channels of this estuary controlling the dispersal of sediment into the system. A 3-year study of morphodynamic equilibrium has been carried out in the tidal channels of Bahía Blanca Estuary with the aim to investigate the evolution of the system. Detailed changes in the spatial bathymetry linked to the observed flow and sediment processes give a clearer indication of the tidal circulation in the channels. This paper discusses morphologic variability and processes of the erosion, deposition and transport of sediment, which determines the morphological evolution of the system. Current measurements showed that channels appeared to be ebb-dominated with peak speeds of up to 1.2 m/s. Examination of current durations suggests that flood-time dominance is about 7 hr, while ebb period is 5 hr. The cross section bathymetry is usually bimodal with two channels separated by a shallow area. The deeper channel experiences ebb-directed net, while the shallower channel could be influenced by the net flood current. The net sediment transport into of these systems is shown to be governed more by the degree of tidal velocity asymmetry (ebb flow). In change the degree of time asymmetry (flood flow) governs the trends of erosion by the longer duration of tidal flood. Channel migration causes a shift from degradation in the north sector to aggradation in the south side, during adjustment. As a consequence, the estimated rate of migration is on the order of 25 m yr−1. Comparing the migration pattern between tidal and fluvial channel, we can to say that in rivers, where the water flows only one way, all morphologic features tend to migrate downstream. In tidal channels, by contrast, the erosive features appear to migrate in opposed directions to the dominant sediment transport direction. It is the erosive processes at tidal channels, which are mainly associated with flood currents dominance.